2003
DOI: 10.1038/sj.onc.1206592
|View full text |Cite
|
Sign up to set email alerts
|

von Hippel–Lindau protein complex is regulated by cell density

Abstract: Mutations in the von Hippel-Lindau (VHL) gene are involved in the VHL family cancer syndrome and sporadic renal cell carcinoma. Previous studies indicated that VHL-induced growth arrest required high cell density and growth on extracellular matrix. In the present study, VHL protein (pVHL) levels were observed to be dramatically increased in cells grown to high cell density compared to cells grown at low cell density. Reverse transcription-polymerase chain reaction and Northern blot analysis indicated that VHL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Previous reports have indicated that VHL affects hnRNP A2/B1 expression, and VHL is also regulated by cell density (42,43). According to the reported observations, we suggest a link between cell density, hnRNP A2/B1 expression, and EMT regulation in nonepithelial cancer cells.…”
Section: Discussionsupporting
confidence: 50%
“…Previous reports have indicated that VHL affects hnRNP A2/B1 expression, and VHL is also regulated by cell density (42,43). According to the reported observations, we suggest a link between cell density, hnRNP A2/B1 expression, and EMT regulation in nonepithelial cancer cells.…”
Section: Discussionsupporting
confidence: 50%
“…Interestingly, the expression of VHL is strictly regulated by cell density where the steady-state amount of VHL in human renal proximal tubule epithelial cells was shown to increase more than 100-fold in dense cultures relative to sparse cultures (3). In addition, other components of the VHL E3 ligase complex showed a similar cell density-dependent regulation (44). Importantly, HIF-2␣ level was elevated in sparsely growing cells with low levels of VHL and significantly reduced or undetectable in confluent cells containing abundant VHL (44).…”
mentioning
confidence: 72%
“…Because the increase in pVHL under hypoxic conditions displayed the greatest stimulation at cell confluence in serum-free medium, our subsequent experiments were carried out under these conditions, where the level of proliferation was low to reduce the contribution of the cell cycle. Also, previous studies indicated that functional VHL induced growth arrest at high cell density (36) and regulated cyclin D1 expression (2,3). Second, the level of pVHL expression was examined by Western blot analysis for various periods of time in normoxic or hypoxic conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%